The Urgency of Granting Authority to Assess Corruption Justice Collaborators - Triwanto Triwanto; Esti Aryani (BESTUUR, 2020)
This study aims to determine the urgency of the authority of investigators in the determination of justice collaborators in criminal acts of corruption. In answering the above problems, the research method used is doctrinal research. This study applies a case approach and concept. While the method of data collection is done by examining case studies and literature studies or mere secondary data. So if the Urgency of Giving the authority of the investigator in questioning the determination of justice collaborator in a criminal act of corruption, the author sees that there are 3 (three) things that become the basis for the urgency of granting authority to determine Justice Collaborator by the investigator, including: a. philosophical, b. juridical, and c. sociological. said to be important because it has become a common perception for investigators and police investigators about the massive and organized circulation of corruption networks at this time, in the investigation process often investigators find the potential of the existence of a saski crown that could become the role of justice collaborator. Keywords: Justice; Justice Collaborator; Corruption.